Indirect immunofluorescence screening of potential arthritic autoantibodies in systemic lupus erythematosus - Selvaraja, Malarvili; Che Ku Daud, Che Ku Dahlan; Abdul Jalil, Marsitah; Md. Shah, Anim; Amin Nordin, Syafinaz; Ahmad Bajari, Zamzarina; Chong, Chou Min; Abdullah, Maha (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2018)
Introduction: Joint involvement is common in systemic lupus erythematosus (SLE) patients, however, screening for joint specific autoantibodies in patients is not routinely performed. This may be due to the lack of known antigens and available tissue. The rat musculoskeletal tissue may be a suitable source of antigen to detect arthritic autoantibodies. Method: We tested plasma of SLE patients, with arthritis (N=9) and without arthritis (N=7) as well as plasma from normal individuals (N=7) on fresh sectioned tissue from rat plantar hind paw using indirect immunofluorescence method. Results: Binding of autoantibodies to striation in skeletal muscle cells in the tissue was clearly demonstrable in all samples from SLE with arthritis but not on slides incubated with plasma from normal or SLE without arthritis. Conclusion: Thus, rat plantar tissue may be suitable for detecting autoantibodies from SLE patients that may be involved in the pathogenesis of lupus arthritis.